2018
DOI: 10.3390/ijms19051398
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Specificity in Members of the Yeast Amino Acid Transporter Family as Parts of Specific Metabolic Pathways

Abstract: In the recent years, molecular modeling and substrate docking, coupled with biochemical and genetic analyses have identified the substrate-binding residues of several amino acid transporters of the yeast amino acid transporter (YAT) family. These consist of (a) residues conserved across YATs that interact with the invariable part of amino acid substrates and (b) variable residues that interact with the side chain of the amino acid substrate and thus define specificity. Secondary structure sequence alignments s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 120 publications
(212 reference statements)
2
10
0
Order By: Relevance
“…Gournas et al (2018) reported that a limited number of amino acid residues located at five transmembrane segments of yeast APC transporters is required for amino acid binding and specificity [69]. The most relevant residues are at transmembrane segment 1 (TM1), with two glycines, which are invariable in 14 aligned sequences of the yeast APC superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…Gournas et al (2018) reported that a limited number of amino acid residues located at five transmembrane segments of yeast APC transporters is required for amino acid binding and specificity [69]. The most relevant residues are at transmembrane segment 1 (TM1), with two glycines, which are invariable in 14 aligned sequences of the yeast APC superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…Several yeast amino acid transporters (YATs) that feature various substrate specificity ranges and affinities help yeast cells to survive in various environments (André 2018;Gournas et al 2016Gournas et al , 2018. Most of these YAT proteins are proton symporters that belong to the APC superfamily (Gournas et al 2016).…”
Section: Ar Antiporters Structures As Templates To Study Eukaryotic Amentioning
confidence: 99%
“…In fungi, amino acids are imported into cells by amino acid permeases (Aaps) located in the plasma membrane. Most yeast Aaps belong to the yeast amino acid transporter (YAT) family, a group of proteins in the amino acid - polyamine-organocation (APC) superfamily [ 17 ]. Aap homologs of the APC superfamily are found in fungi as well as animals, plants, and bacteria [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical YAT possesses 12 transmembrane regions (TMs) and functions as a symporter through proton-driven secondary active transport [ 19 , 20 ]. In the yeast Saccharomyces cerevisiae , 19 Aaps have been identified [ 17 ]. The yeast Aaps have different substrate specificities.…”
Section: Introductionmentioning
confidence: 99%